MONITORING OF PRODUCTION WELL PERFORMANCE IN ULUBELU GEOTHERMAL FIELD USING FLOW PERFORMANCE TEST METHOD - Permadi Sugiharto, Mochamad
Monitoring the wells performance in Ulubelu field is very important to maintain the continuity of steam supply to the power plant. One aspect that is monitored in monitoring well performance is by updating deliverability curve model of production well. The thing that needs to be done to update the well deliverability curve model is to perform periodic production tests. However, this method is not possible due to limited steam buffer in Ulubelu Field. An alternative solution that can be used to update the production well deliverability curve without having to leave the gathering system is the Flow Performance Test (FPT) method. This research is conducted to determine the performance of production wells, so that the data obtained will be developed into a deliverability curve model. FPT is applied to wells located in clusters D, J and K. The data obtained is validated with TFT data or production test data where the deviation of the data obtained for UBL-DLX1 is 4%, UBL-DLY42 is 0.7%, UBL-DLZ15 is 3%, UBL-JLW23 is 4% and UBL-KLT64 is 0.3%. Model evaluation of the UBL-DLX1 and UBL-DLY42 wells shows the performance of the wells that have not recovered after work over, while UBL-DLZ15 seems to experience a natural decrease in production. The models formed from FPT in UBL-JLW23 and UBL-JLV83 are used as the basis for the well performance monitoring model. Evaluation of UBL-KLT64 shows that there is a problem in the wellbore or reservoir. Based on the results of this study, the FPT method is reliable enough to be used as an alternative in monitoring the performance of production wells, so that it can be recommended as one of routine work in well surveillance program.